Agenda for Africa's economic renewal (US Third World policy perspectives, 1996)
In Agenda for Africa's Economic Renewal, ten experts from Africa, Europe, and the United States look beyond structural adjustment and identify the strategic elements that are needed to engineer Africa's economic recovery in the coming years. Starting from the considerable degree of consensus among policymakers and scholars about what ails African economies, the authors analyze the key choices that need to be made in the critical areas of agriculture, trade and industry, state capacity, and the social sectors. The authors consider these strategic priorities in the extremely fragile environment of democratic rule in many countries of the region, and they stress the long overdue need to focus directly on the political implications of economic policy choices.